Word 2013 for Dummies e Learning Kit : A Wiley Brand - Lowe, Lois (Hoboken, New Jersey John Wiley & Sons, 2013)
Takes you through the basics of the Word interface and explains how to navigate it, how to get comfortable with the terminology, and how to use its many features. This book helps self-motivated learners master Word 2013, the most popular word processing application.
Include Illustration, Appendix and Index
Keywords: Word processing -- Microsoft Word